1963
DOI: 10.1002/path.1700850117
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic and hyperplastic changes in the alimentary canal of the lactating rat

Abstract: DURING lactation in the rat the alimentary canal shows an increase in weight and nitrogen content compared with that of unmated controls (Poo, Lew and Addis, 1939), or pregnant rats (Boyne, Chalmers and Cuthbertson, 1953; Souders and Morgan, 1957). Po0 et al. included with the alimentary canal the entire contents of the abdomen and pelvis except for the liver, kidneys and uterus, whereas Boyne et al. examined the cleaned and empty gut and Souders and Morgan studied only the small intestine. The determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
94
1

Year Published

1970
1970
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(110 citation statements)
references
References 10 publications
15
94
1
Order By: Relevance
“…Addition of dihydroxyacetone (5mM), which was found by Harris (1975) (Panek etal., 1977) and female (Harris, 1975;Mapes, 1977) rats which have been meal-fed with a low-fat high-carbohydrate diet, but in the present experiments we did not wish to interfere with the normal dietary regime of the rats. It is well established that lactating rats have a higher food intake than virgin rats (Cole & Hart, 1938;Fell et al, 1963) and this may play a role in the increased rate of lipogenesis. As expected, oleate (1 mM) decreased both the rate of endogenous lipogenesis (Table 1; Mayes & Topping, 1974) and that in the presence of dihydroxyacetone.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of dihydroxyacetone (5mM), which was found by Harris (1975) (Panek etal., 1977) and female (Harris, 1975;Mapes, 1977) rats which have been meal-fed with a low-fat high-carbohydrate diet, but in the present experiments we did not wish to interfere with the normal dietary regime of the rats. It is well established that lactating rats have a higher food intake than virgin rats (Cole & Hart, 1938;Fell et al, 1963) and this may play a role in the increased rate of lipogenesis. As expected, oleate (1 mM) decreased both the rate of endogenous lipogenesis (Table 1; Mayes & Topping, 1974) and that in the presence of dihydroxyacetone.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently mice ingested feed at full ingestive capacity in the first and second weeks of lactation, but this capacity increased in the second week. Fell et al [12] found that the alimentary canal of lactating primiparous rats increased progressively in weight, size and total nitrogen content up to weaning, after which there was a decline. Macroscopic hypertrophy of the alimentary canal, particularly of the small intestine and caecum, was remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this failure is that previous studies have tended to measure BMR in pre-reproductive animals. Lactating mice show considerable morphological plasticity during lactation relative to the situation when they are virgins, including expansion of their alimentary tracts and liver sizes (Fell et al, 1963;Kennedy et al, 1958) with associated modulations of their resting metabolic rates (Speakman and McQueenie, 1996). Previously pregnant mice have a greater body mass, attributed to protein accumulation, than nonparous mice (Holinka, 1980).…”
Section: Introductionmentioning
confidence: 99%